2020
DOI: 10.1111/ijfs.14572
|View full text |Cite
|
Sign up to set email alerts
|

Effects of impregnate temperature on extraction of caffeoylquinic acid derivatives from Moringa oleifera leaves and evaluation of inhibitory activity on digestive enzyme, antioxidant, anti‐proliferative and antibacterial activities of the extract

Abstract: SummaryIn an ultrasonic bath and for 30 min in the presence of water as extraction solvent in a ratio of 1:10 (g/mL), effect of extraction temperature on extraction of caffeoylquinic acids (CQAs) from Moringa oleifera leaves (MOL) was investigated. Gradually increasing in extraction temperature caused a growing in mono‐CQA and declining in 3,5‐diCQA. The extract obtained at 80 °C showed the highest antioxidant capacity, and IC50 values for scavenging activities on DPPH radicals and ABTS radicals were 56.9 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 39 publications
2
20
0
Order By: Relevance
“…Furthermore, these values were about 46.5-55.3 times and 42.5-48.9 times, respectively, lower than that of the control (29.31 mg/ml, Table 2). The lower DPPH IC 50 value indicated a greater free radical scavenging activity (Hamed et al, 2020;Kovarova et al, 2013;Sebaugh, 2011) (Arina & Harisun, 2019;Hwang et al, 2010). Kong et al, (2009) reported that ginseng pretreated with acid, especially citric acid, had an increased phenolic content compared with that of the control, which was also observed in this study (Table 2) Note: Values were expressed as mean ± standard deviations (n = 3 independent experiments).…”
Section: F I G U R Esupporting
confidence: 79%
See 1 more Smart Citation
“…Furthermore, these values were about 46.5-55.3 times and 42.5-48.9 times, respectively, lower than that of the control (29.31 mg/ml, Table 2). The lower DPPH IC 50 value indicated a greater free radical scavenging activity (Hamed et al, 2020;Kovarova et al, 2013;Sebaugh, 2011) (Arina & Harisun, 2019;Hwang et al, 2010). Kong et al, (2009) reported that ginseng pretreated with acid, especially citric acid, had an increased phenolic content compared with that of the control, which was also observed in this study (Table 2) Note: Values were expressed as mean ± standard deviations (n = 3 independent experiments).…”
Section: F I G U R Esupporting
confidence: 79%
“…Furthermore, these values were about 46.5–55.3 times and 42.5–48.9 times, respectively, lower than that of the control (29.31 mg/ml, Table 2). The lower DPPH IC 50 value indicated a greater free radical scavenging activity (Hamed et al., 2020; Kovarova et al., 2013; Sebaugh, 2011) of the treated ginseng samples compared to the control. The total phenolic content increased from 2.08 to 39.00–40.12 mg GAE/g (18.8–19.2 times higher) and 36.54–37.50 mg GAE/mg (17.6–18.0 times higher), respectively, for the treated ginseng samples without and with steam treatment (Table 2).…”
Section: Resultsmentioning
confidence: 98%
“…These compounds have been reported to exhibit antioxidant (Hamed et al. , 2020; Nzekoue et al. , 2020; Trendafilova et al.…”
Section: Introductionmentioning
confidence: 99%
“…The most abundant form of chlorogenic acid in nature is 5-caffeoylquinic acid (Olthof et al, 2001). Chlorogenic acid isomers (3-caffeoylquinic, 4-caffeoylquinic, and 5caffeoylquinic acids) show many biological activities such as antibacterial, antioxidant, anticarcinogenic, hypoglycaemic, hypolipidemic, hepatoprotective, antihistamine antimutagenic, anti-obesity, antidiabetic, antiviral, anti-Alzheimer, neuroprotective (Clifford et al, 2017;Hamed et al, 2020;Matthews et al, 2020;Torres et al, 2021). Rutin is a flavonoid found in many plants, also considered a non-toxic chemical that may be useful in biomedical applications and showing biological activities such as anti-inflammatory, anticarcinogenic, antioxidant, neuroprotective, cytoprotective, vasoprotective, cardioprotective, and hepatoprotective (Ghorbani, 2017;Shahi et al, 2019).…”
Section: Figure 2 Gc-ms Profile Of Helichrysum Pallasii Leavesmentioning
confidence: 99%